Removal of an azo dye (Orange G) from aqueous solution using modified sawdust - Banerjee S.; Chattopadhyaya M.C.; Sharma Y.C. (My University, 2025)
In the present study, modified sawdust was used for the removal of an azo dye (Orange G (OG)) from aqueous solutions. The study was carried out in batch mode. Effects of various important parameters such as pH, concentration, temperature, dose and agitation speed on the removal of the dye were investigated for optimization of the process. It was observed that the maximum removal of 78.3% was achieved at the lowest dye concentration of 50 mg/L. The process of removal was found to be exothermic in nature. Adsorption of OG on modified sawdust was rapid and in accordance with pseudo-first-order kinetics. Mass transfer coefficient (βL) was also estimated and found to be 0.33 cm/sec at 30 WC, which indicates that sorption of dye was driven by a film diffusion mechanism. The Langmuir isotherm model agrees well with the sorption isotherm data and also confirms that adsorption took place on the homogenous surface of modified sawdust. The Langmuir capacity was determined and found to be 5.48 mg/g. Therefore, the study recommends that modified sawdust is a promising candidate for the efficient removal of dye-contaminated wastewater. © IWA Publishing 2015.